An Influence of Knowledge Management to the Intellectual Capital and the Effect to the Competitive Advantage (Sains Humanika, 2021)
The extremely intense competition in education requires each Private Universities to have competitive advantages, where one of them is high intellectual capital, which can provide value to its customers. One of the influencing factors in the improvement of intellectual capital is namely the existence of effective knowledge management activities on PTS. This research intends to examine and analyze the effect of knowledge management on the intellectual capital, and the influence of intellectual capital on competitive advantage in the private universities. The research methods applied the explanatory survey, causal relationship, and verification method. The research population is PTS Kopertis Region IV. The sampling technique uses proportional probability sampling, where the sample size was determined by using power analysis approach test. Data collection was carried out by interview, observation, and questionnaire techniques that have been tested for validity and reliability. The analytical test applied SEM (Structural Equation Model)-LISREL 8.3, the second-order approach. The research result concluded that knowledge management has a significant impact on intellectual capital, intellectual capital has a significant impact on competitive advantage, and knowledge management significantly influences competitive advantage on the PTS through its intellectual capital.Â Â
Keywords: Competitive advantage; intellectual capital; knowledge management